Fundamentals of biochemistry - Voet, Donald (John Wiley & Sons, 1999)
Includes up-to-date coverage on human health and disease. Uses simple, clear language to convey the inspiring beauty of the structure and chemistry of life. Early emphasis on recombinant DNA technology.